Traditions of the Enlightenment French Philosophical Prose in the Modern Belarusian Philosophical-Allegoric Novel - Жилевич, Ольга; Гагуа, Руслан (Poznańskie Studia Slawistyczne, 2018)
Some Belarusian philosophical-allegoric novel renewal periods have been studied closely with the emphases on the historic, social and cultural heritage of different epochs. In the article, the decisive role of the Enlightenment French philosophical prose is noted in the development of the modern Belarusian philosophical-allegoric novel. The Enlightenment French philosophical-allegoric text is a model of reality, simple for understanding, with a fascinating adventure story, but with an obscure moral and philosophical attitude and didacticism. The 18th century philosophical-allegoric prose is distinguished by the parable form of narrative, which is characterized by moral and philosophical problems, global questions about the life and destiny of people, marked by didacticism, by a high degree of generalization, and the obligatory projection of the idea on the reader views. The article proves the influence of Montesquieu, Voltaire, and Diderot’ philosophical works on the development of the modern philosophical-allegoric novel in Belarusian literature. The article analyzes the poetics of Belarusian contemporary works of this genre taking into account the French traditions of the Enlightenment.